Ulul Albab: The Concept of Perfect Intelligence in Islam: Theoretical Review and Application in Islamic Psychology - Dian Sandi Utama (CV. Publikasi Indonesia, 2024)
Allah as the Creator of the universe, including human beings, has bestowed the brain and intellect including the heart (qalbun) to humans as His great gift. This is what distinguishes humans from other creatures in this universe. Man becomes a perfect creature because he can think and feel or have lust (will). Perfection can make the human being the best creature if he can maximize the potential that Allah gives in him. Nevertheless, humans can also become the most despicable creatures even more than animals if they cannot harness this potential in the path of goodness. In maximizing this potential, Allah provides guidance in the holy book of the Qur'an. As a manual book, the Qur'an is the perfect book to be explored and guided in maximizing the power possessed by humans, including the aspect of intelligence. The research uses a qualitative approach with the type of research being literature research. The result of this research is that Ulul albab became a term used by Allah to describe this intelligence. The figure of ulul albab is a Muslim human being who is strong in his thinking in using the potential of his intellect, strong in dhikr in forming spiritual intelligence which will eventually have good emotions or the ability in emotion management or emotional intelligence. Therefore, it is very appropriate to mention that ulul albab is the concept of perfect intelligence.